PERAN SUAMI DAN AKSES INFORMASI KELUARGA BERHUBUNGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI - Ronasari Mahaji Putri; Lidia Laka Bora (AKPER Pasar Rebo, 2021)
The phenomenon of low exclusive breastfeeding by mothers is associated with the husband's less role and low access to family information. The research objective was to determine the relationship between husband's role and access to family information with exclusive breastfeeding for infants aged 0-6 months at Posyandu for Toddlers at Kendalsari Public Health Center, Lowokwaru District, Malang City. The research design used a correlative design with a cross sectional approach. The population numbered 35, with a sample of 32 people, taken by simple random sampling technique. The research instrument used a husband's role questionnaire, access to family information and exclusive breastfeeding. Data analysis using Chi Square. The results of the study prove that half of the respondents, namely 16 (50.0%), have a lack of husband's role in exclusive breastfeeding, almost half of 15 (46.9%) respondents have less access to family information and most of the 17 (53.1%) respondents provide Non-exclusive breastfeeding for infants aged 0-6 months. The results of the Chi Square test show that there is a relationship between the husband's role and access to family information with exclusive breastfeeding for infants aged 0-6 months at the Posyandu for Toddlers at Kendalsari Public Health Center, Lowokwaru District, Malang City (p value = 0.000). It is recommended for further research to provide health education about exclusive breastfeeding to mothers who have children aged 0-6 months, so that mothers are motivated to give breast milk to their children.